1987
DOI: 10.1172/jci112972
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human endothelial cell proliferation by gold compounds.

Abstract: Neovascularization has a role in the propagation of rheumatoid synovitis because the spread of mononuclear cell infiltration and the growth of pannus are dependent on the growth of new blood vessels. Growth of such vessels requires local endothelial cell (EC) proliferation. Inhibition of synovial EC proliferation, therefore, would have the potential to diminish rheumatoid inflammation. We have, therefore, studied the effects of gold sodium thiomalate (GST), auranofin, and gold chloride on the proliferation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 39 publications
0
22
0
2
Order By: Relevance
“…These include cytokines, such as basic fibroblast growth factor (bFGF) (5), interleukin-8, and vascular endothelial growth factor, and soluble adhesion molecules, such as vascular cell adhesion molecule and Eselectin (6). Interestingly, many of the available treatments for RA have been shown to possess some degree of antiangiogenic activity (7)(8)(9). In fact, treatments that suppress the angiogenic process may favorably impact disease course, as suggested by studies in an adjuvant-induced model of arthritis (10).…”
Section: Introductionmentioning
confidence: 99%
“…These include cytokines, such as basic fibroblast growth factor (bFGF) (5), interleukin-8, and vascular endothelial growth factor, and soluble adhesion molecules, such as vascular cell adhesion molecule and Eselectin (6). Interestingly, many of the available treatments for RA have been shown to possess some degree of antiangiogenic activity (7)(8)(9). In fact, treatments that suppress the angiogenic process may favorably impact disease course, as suggested by studies in an adjuvant-induced model of arthritis (10).…”
Section: Introductionmentioning
confidence: 99%
“…GSTM inhibits monocyte oxygen radical generation (19) and Fc and C3 receptor expression and chemotaxis (20). Moreover, GSTM has effects on endothelial cells including inhibition of cell proliferation (21) and HLA-DR expression (22).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that EC are more sensitive to CCA than are synovial fibroblasts. We (28) and others (29) have reported that gold sodium thiomalate inhibits the proliferation of EC. It has also been shown that D-penicillamine and methotrexate inhibit both basal and endothelial cell growth factor (ECGF)-stimulated DNA synthesis by human EC in vitro and suppress ECGF-induced neovascularization in vivo (30,3 1).…”
Section: Discussionmentioning
confidence: 75%